Performance study of the Memory Utilization of an Improved Pattern Matching Algorithm using Bit-Parallelism - Oladunjoye, John Abiodun; Timothy, Moses; James, Okpor; Raphael, Baku Agyo (ICSE (Institute of Computer Sciences and Engineering), 2022)
The strategy of packing several data values in a single computer word and refreshing them all in a solitary operation is referred to bit parallelism. It assumes a significant part in pattern matching because it can handle in parallel the length of pattern sizes. In this paper, an Improved Pattern Matching model (IPM) proposed, which makes searching process quicker and decreases how much memory used in processing input data. C Sharp was used for the development of the model. With a computer word size of 64bits and pattern length ranging from 8 characters to 72 characters, the system decides how much memory is used. The developed model was evaluated and contrasted with the existing model using 64bits computer word size (cws) and the pattern length of 72 characters. The assessment showed that the IPM had minimal worth of MU contrasted with the existing model (BNDM, SBNDM, and FSBNDM). This IPM model can be embraced for improvement of the size of string data stored in computer word because of its capacity to diminish memory space usage.